Assessment of knowledge, attitude, and practice towards research ethics among medical faculty and postgraduate residents of the government medical college in Uttarakhand - Garhwal, Karishma; Bartwal, Janki; Rawat, Chandra Mohan Singh; Nautiyal, Nidhi (Indian Journal of Community Health, 2025)
Background: Research ethics fundamentally describe the guidelines followed by a researcher while working on the research. This study assesses the knowledge, attitude, and practices towards research ethics among medical faculty and postgraduate residents. Methods: 105 medical faculty and postgraduate students participated in a cross-sectional study at a government medical college in Uttarakhand using convenience sampling. A semi-structured questionnaire was used to gather data, which included demographics, knowledge, attitudes, and practices related to research ethics. Participants were approached department-wise and provided a Google Form link. Statistical analysis was conducted using SPSS version 20, with p < 0.05 considered significant. Results: Of the 105 participants, 66.6% were ?30 years old, 53.3% were female, and 64.8% were postgraduate residents. While 68.6% were currently involved in research, 64.8% had no prior publications. Knowledge of research ethics varied significantly by rank, with faculty and senior residents demonstrating stronger ethical stances than junior residents, particularly regarding citation practices and method reuse. Significant differences were found in views on self-plagiarism, plagiarism severity, and its justification. Reported plagiarism practices included 2.9% using others' work without citation and 4.8% misappropriating ideas. Conclusion: Our study reveals gaps in research ethics awareness, especially among junior residents. While most participants were engaged in research, many lacked prior publication experience. Ethical knowledge varied by rank, with faculty and senior residents demonstrating stronger adherence. Misconceptions about self-plagiarism and plagiarism severity were common, highlighting the need for targeted ethics training.